Pengaruh Peningkatan Dosis Pupuk Hayati VP3 dan Lama Induksi Listrik Terhadap Agregasi Tanah, Pertumbuhan dan Hasil Tanaman Kedelai (Glicine max (L) Merr.) - Dhurrotul Roaidha; Indiyah Murwani; Novi Arfarita (Folium : Jurnal Ilmu Pertanian, 2021)
This research was conducted to determine the effect of increasing dose of VP3 biofertilizer and duration of electrical induction on soil aggregation and yield of soybean (Glycine max (L) Merr.). This research was conducted at Griya Santa Brawijaya University Malang and Central Laboratory, Islamic University of Malang from October 2020 to January 2021. This study used a Randomized Block Design (RAK) with 13 treatments and was repeated 3 times. Observational data were analyzed using the 5% level F test (ANOVA). If there is a significant effect, then further testing is carried out with DMRT (Duncan Multiple Range Test) at 5% level. The results showed that the NL2 (100% NPK + 60 minutes electric induction) treatment was the treatment with the highest average value for the plant height parameter, and the V1L3 treatment (100% VP3 biofertilizer + 90 minutes electrical induction) was the treatment with the highest value. the highest average of leaf area parameters, while on soybean yields the V1L2 treatment (100% VP3 biofertilizer and 60 minutes electrical induction) and V2L1 (200% VP3 biofertilizer and 30 minutes electrical induction) treatments showed the best results on soil aggregation and soybean yields. Soybean yields were shown in the parameters of the percentage of flower pods, dry weight of seed harvest, oven dry weight of seeds, and weight of 100 seeds.